ANALISIS PENGEMBANGAN KARAKTER PELAJAR PANCASILA MELALUI PENERAPAN KURIKULUM MERDEKA BELAJAR DI SD NEGERI TANDES KIDUL I NO. 110 KOTA SURABAYA - Suhartono; Bernadetta Budi Lestari; Indah Novitasari (Holistik Analisis Nexus, 2024)
The implementation of this research is to find out the application and development of the character of Pancasila through the implementation of the independent learning curriculum at SD Negeri Tandes Kidul I No. 110 Surabaya City. The qualitative approach used in this study. Observation and data collection will be carried out from January to April 2024. SD Negeri Tandes Kidul I No. 110 Surabaya City is the place where the data is collected. Results in this study: The value of Pancasila character developed through the implementation of the independent curriculum at SD Negeri Tandes Kidul I No. 110 Surabaya City is not optimal; this is evidenced by the results of observation where not all students practice the developed Pancasila character. 10 out of 18 class teachers said that the development of Pancasila character in the implementation of the independent curriculum requires a long time and process. In addition, the implementation of the independent curriculum policy in schools is also still found to be found many obstacles, including Teachers still do not understand the independent curriculum policy, there is still confusion in implementing the independent curriculum. This is not without reason, one of which is because there are not too many trainings and workshops on the independent learning curriculum, teachers are also busy with quite a lot of administrative tasks.